Comparing continuous control policies by modeling and simulation of the procurement process - Douraid, Abdessamad; Ech-Cheikh, Hamid; El Had, Khalid; Laradi, Mohamed (International Journal of Engineering and Technology, 2020)
Inventory management is a challenging problem area in supply chain management and companies need to have inventories in warehouses in order to satisfy customer's needs. Meanwhile, these inventories have holding costs and this is a frozen fund that can be lost. Therefore, the task of inventory management is to find the right quantity of inventories that will fulfill the demand with the right price, avoiding overstocks. The aim of this paper is to carry out a comparing study of continuous inventory control policies in a stochastic environment of demand and lead time, in order to find out the impacts of the decision variables of each inventory control policy. For this purpose, the discrete event simulation approach has been chosen to generate various scenarios of inventory control policies of the procurement process by taking into account the production planning of the manufacturing company. The comparison of these configurations based on the essential key performance indicators of the supply chain, namely the cost and service level.Â Â